2010
DOI: 10.2474/trol.5.52
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fretting Protection Property of Lubricating Grease Applied to Thrust Ball Bearing

Abstract: Fretting wear is often the case when ball-and-roller bearings oscillate under grease lubrication. Against the backdrop of fretting wear on the wheel bearings of automobiles caused by rail transportation, the ASTM D4170 fretting test method was developed to evaluate the fretting protection property of lubricating grease. The ASTM test is conducted under a fixed load, but the load condition for industrial machines usually fluctuates. Currently, there is no international standard to evaluate the fretting wear und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Table 1 summarizes the main properties of the greases. All greases have similar density between 0.88-0.9 g/cm 3 . In this study, 4 types of new and unworked greases were used in the experiments, as this replicates the starting condition in which bearing assemblies would leave their place of manufacture.…”
Section: Grease Lubricantsmentioning
confidence: 97%
See 2 more Smart Citations
“…Table 1 summarizes the main properties of the greases. All greases have similar density between 0.88-0.9 g/cm 3 . In this study, 4 types of new and unworked greases were used in the experiments, as this replicates the starting condition in which bearing assemblies would leave their place of manufacture.…”
Section: Grease Lubricantsmentioning
confidence: 97%
“…Pittroff [19] reported that soft grease is less effective for fretting wear reduction due to its weak shear strength and adhesiveness. Contradicting results published by Yan et al [3] and Kita and Yamamoto [20] showed soft grease is more effective due to the higher uidity of the base oil. Recent work done by Maruyama et al [17] highlighted the grease with high bleed oil does not contribute to fretting wear reduction when A/D >1; because the worked thickener entered the contact and formed a layer to reduce the fretting wear.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…False brinelling, a form of fretting wear, mainly occurs when a lubricated rolling bearing is stationary during transport either by sea or rail [1,2]. The identification of false brinelling is by the elliptical wear marks on the raceways in the axial direction at each roller position [3]. The false brinelling marks are caused by micromovements due to very low-amplitude oscillation/ vibration between the rolling elements and the raceways.…”
Section: Introductionmentioning
confidence: 99%
“…Vadean et al 24 concluded that the bearing wear was minimum under a certain negative clearance on the pitch wheel bearing. Yano et al 25 tested 14 types of commercial grease and 3 types of special grease with thrust ball bearings. They compared the results of the ASTM micro-test against an impact micro-test (thrust varying sinusoidally between 1.96 and 88.2 kN) to evaluate the fretting wear protection properties of these greases.…”
Section: Introductionmentioning
confidence: 99%